Aboriginal Languages in Quebec: Fighting Linguicide with Bilingual Education - Taylor, Donald M.; Caouette, Julie; Usborne, Esther; Wright, Stephen C. (Diversité urbaine, 2008)
Aboriginal peoples in Quebec are fighting for the survival of their language and culture. An essential component of Aboriginal decolonization and empowerment is the protection and enhancement of the Aboriginal heritage language. In this article, we review twenty years of research in Arctic Quebec (Nunavik) involving Inuit students educated in Inuktitut as well as in French and English. Our research reveals that children not only learn better in their own heritage language as opposed to one of the societally dominant languages, but also develop a more positive view of themselves, and a healthier view of Inuit as a group. Bilingual Education is shown to be of crucial importance for the vitality of Inuit language and culture. Les peuples autochtones du Québec luttent afin de préserver la survie de leur langue et de leur culture. Un élément essentiel de la décolonisation et de l’autonomisation autochtone est la protection et l’enrichissement de la langue ancestrale autochtone. Dans cet article, nous effectuons une analyse de vingt années de recherche dans le Nord du Québec (Nunavik) impliquant des élèves inuits scolarisés en français et en anglais. Nos recherches ont révélé que ces enfants non seulement apprennent mieux dans leur propre langue ancestrale plutôt que dans une des langues dominantes de la société, mais aussi qu’ils développent une image d’eux-mêmes plus positive, et une représentation plus saine des Inuits en tant que groupe. Il est démontré que l’enseignement bilingue est d’une importance cruciale, contribuant à la vitalité de la langue et de la culture inuites.